Psychometric evaluation of the Arabic version of the nomophobia questionnaire: confirmatory and exploratory factor analysis - implications from a pilot study in Kuwait among university students - Al-Balhan, Eisa M; Khabbache, Hicham; Watfa, Ali; Re, Tania Simona; Zerbetto, Riccardo; Bragazzi, Nicola Luigi (Psychology research and behavior management, 2018)
In the past decades, thanks to the widespread use of the new information and communication technologies, nomophobia has emerged as a contemporary psychological disorder. More in detail, it has been defined as the modern fear of feeling disconnected, being out of mobile phone contact, and being unable to access information and/or communicate with others. Few authors have used an Arabic version of the Nomophobia Questionnaire, even though its psychometric properties are not well known and have been poorly investigated from a formal rigorous standpoint. Our research objective was to develop and validate the Arabic version, administering it to a sample of adolescents and young adults in a country characterized by a high mobile network coverage. A total of 512 subjects (aged 21.62±4.33 years, median 20 years), equally distributed between males and females, and based in Kuwait, volunteered to take part in the study. The confirmatory factor analysis did not show a completely satisfactory fitting with the original factor structure. The exploratory factor analysis showed that four factors had 57.24% variance. Overall Cronbach's alpha coefficient was 0.879. However, the coefficient increased from 0.645 to 0.849 with respect to the original factor structure. Scores (and mean scores) were 4.25±1.59 (21.23±7.95), 2.95±1.33 (17.68±7.97), 4.48±1.78 (8.96±3.56), and 4.98±1.52 (34.84±10.67) for factors I, II, III, and IV, respectively, whereas the overall score (and mean overall score) was 4.14±1.13 (82.71±22.68). In our sample, no subject (0.0%) was without nomophobia, with 92 (18.0%) and 288 individuals (56.2%) reporting mild and moderate nomophobia levels, respectively. Approximately a quarter of the recruited sample (132 subjects, 25.8%) had severe nomophobia level.